An ecological-economic model of land-use decisions, agricultural production and biocontrol. Issue 10 (5th October 2022) - Martinet, V.; Roques, L.
Abstract : The regulation of agricultural pests by their natural enemies is a key step in the agroecological transition. The level of biocontrol seems, however, to highly depend on the agronomic and ecological context. It is thus important to identify the conditions under which this ecosystem service is efficient as well as the magnitude of its effects. An actual reduction of pesticide use depends on a change in farmers' decisions, calling for the consideration of economic dimensions. We develop a dynamic agroecological-economic model representing land-use and agricultural intensity decisions as well as the dynamics of a crop pest and a natural enemy. Biocontrol is assessed considering both private benefits (increase in farmers' profit) and public benefits (reduction of pesticide use) with respect to a situation without a natural enemy. We provide a theoretical assessment of the magnitude of biocontrol over a wide range of agronomic contexts (spatially explicit maps of agricultural production potential, with heterogeneous distribution and control of spatial fragmentation) and ecological contexts, described through various parameter values of a reaction–diffusion model. The contexts in which biocontrol plays a significant role are identified, and the role of key parameters is discussed. Our open-access model offers a tool to investigate alternative specifications.